Burst Format Design for Optimum Joint Estimation of Doppler-Shift and Doppler-Rate in Packet Satellite Communications. (6th May 2007) - Giugno Giugno, Luca Luca; Zanier Zanier, Francesca Francesca; Luise Luise, Marco Marco
Abstract : This paper considers the problem of optimizing the burst format of packet transmission to perform enhanced-accuracy estimation of Doppler-shift and Doppler-rate of the carrier of the received signal, due to relative motion between the transmitter and the receiver. Two novel burst formats that minimize the Doppler-shift and the Doppler-rate Cramér-Rao bounds ( CRB s) for the joint estimation of carrier phase/Doppler-shift and of the Doppler-rate are derived, and a data-aided (DA) estimation algorithm suitable for each optimal burst format is presented. Performance of the newly derived estimators is evaluated by analysis and by simulation, showing that such algorithms attain their relevant CRB s with very low complexity, so that they can be directly embedded into new-generation digital modems for satellite communications at low SNR.